Modifications in Aortic Stiffness After Endovascular or Open Aortic Repair: A Systematic Review and Meta-Analysis. (April 2022) - Bissacco, Daniele; Conti, Michele; Domanin, Maurizio; Bianchi, Daniele; Scudeller, Luigia; Mandigers, Tim J.; Allievi, Sara; Auricchio, Ferdinando; Trimarchi, Santi
Abstract : Objective: Increased aortic stiffness (AoS) has been recognised as a risk factor in the development of cardiovascular disease. The aim of this systematic review and meta-analysis was to assess the impact of aortic repair on AoS. Data Sources: PubMed, Scopus, and Web of Science were searched systematically for relevant studies evaluating the consequences of endovascular and open aortic repair on AoS. Review Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P) statement was followed to perform the research process. Papers containing data on AoS before and after both thoracic (TEVAR) and abdominal (EVAR) endovascular repair, as well as open surgical repair (OSR), were included for detailed evaluation. A fixed effects model was used to perform analysis. The Newcastle–Ottawa Scale was calculated for each included study. Results: The first article cluster comprised 367 papers. After removal of duplicates and the adoption of inclusion/exclusion criteria, 14 articles remained, 13 of which were selected for meta-analysis. Ten studies analysed EVAR and three analysed TEVAR. Five of the selected papers were case control studies, with OSR adopted in four of these as the EVAR comparator. Several graft types were used in the endovascular group. AoS increased after TEVAR and EVAR, in terms of pulse wave velocity (PWV), even though several spatial levels and measurement modalities were adopted. No differences were described after OSR, although no pooled data could be analysed. Conclusion: EVAR and TEVAR both demonstrated a significant increase in AoS measurement (PWV). Although the heterogeneity and the low number of available studies limit the strength of the results, this review highlights the potential deleterious endograft role in the cardiovascular system although further studies are needed to achieve robust evidence. Further studies are needed to improve the mutual interaction between aorta and endograft, minimising their impact on the native aortic wall properties.